Small and medium enterprises in India : infirmities and asymmetries in industrial clusters - Roy, Satyaki (New York : Routledge, 2013)
"Small and Medium Scale Enterprises (SME) have found more interest in the last few years, whereas industrialization is no longer seen as a simple way of development. This book analyses how SME clusters emerge in a developing economy. Using India as a case study, it addresses one central question: If growth has largely failed to be inclusive so far, and if employing work force in increasing returns activities through a different trajectory of industrialization largely dependent upon industrial clusters of SMEs is believed to be true, then what are the structural infirmities and asymmetries that need to be taken into account in the context of framing policies related to industrial clusters? The book identifies the structural infirmities in industrial clusters in India, which could be typical to any of the developing countries and sharply in contrast to European success stories. Blending theory and empirical material, it provides a middle ground between the two extremes of a uniform policy assuming 'one size fits all' and a specific policy based on individual cases. The book redraws the broad contours where space and production processes mutually constitute each other in a typical way giving rise to outcomes something generic to underdevelopment. It is of interest to academics working in the fields of economics, business administration/management and development economics"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Small business -- India; Industrial clusters -- India; Electronic books